A Novel Adaptive Propulsion Enhancement eXperience (APEX) System: Development and Preliminary Validation for Enhancing Gait Propulsion in Stroke Survivors - Seoung Hoon Park; Hyunje Park; Jooeun Ahn; Beom-Chan Lee (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2025)
This study presents the development and preliminary validation of a novel system, called APEX (Adaptive Propulsion Enhancement eXperience), which aims to enhance gait propulsion in stroke survivors. The APEX system utilizes a dual-belt instrumented treadmill capable of measuring ground reaction forces and modulating belt speed in real time to provide visual biofeedback with dynamic propulsion promotion. We developed two propulsion promotion modes: the propulsion-facilitating mode, which extends ground contact time to elicit intrinsic propulsive effort and the propulsion-augmenting mode, which increases propulsive force by applying controlled external force. Ten chronic-stage stroke survivors (7 females and 3 males; age: $61.40~± ~6.96$ years) completed two experimental trials: one with the propulsion-facilitating mode, and the other with the propulsion-augmenting mode. Each trial included a baseline period without assistance (visual biofeedback and propulsion promotion) for 30 steps, a training period with assistance for 100 steps, and a post-training period without assistance for 30 steps. For each period, outcome measures (propulsive force, impulse, lower-limb kinematics, and muscle activity) were quantified. Statistical analysis revealed significant improvements in propulsive force, impulse, lower-limb kinematics, and muscle activity during both the training and post-training periods compared to the baseline period, with no significant differences between the training and post-training periods. These findings demonstrate the efficacy and reliability of the APEX system in delivering real-time, adaptive training to enhance gait propulsion. Integrating the APEX system into clinical practice has the potential to provide a scalable, patient-specific approach for post-stroke gait rehabilitation.